Kewirausahaan: Membangun Ide Bisnis dengan Business Model Canvas - Lisandri Lisandri; Lydia Goenadhi; Hanifah Hanifah; Akhmad Yafiz Syam; Lukas Kaharapen; Fajar Halim Budiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The purpose of this community service is to strengthen entrepreneurship character education and training to develop business ideas for class XII students of SMA Frater Don Bosco Banjarmasin. This school has a mission to develop entrepreneurial interest and develop entrepreneurial character for students. The biggest problem in developing entrepreneurial character is a lack of motivation and lack of creativity and innovation of business ideas. This activity used a training and tutorial approach to 65 participants. Participants were trained and motivated to have a high entrepreneurial spirit and trained in the use of Business Model Canvas (BMC) in mapping business ideas and validating these ideas to their developing business plan. After the post-test, the following conclusions were obtained: 1). Participants know and understand the importance of the role of an entrepreneur; 2.) Participants are motivated and able to explore business ideas creatively and test their feasibility; 3) Participants are able to use BMC as a tool to realize business ideas on paper (canvas) in detail and systematically; 4) Participants understand 9 important elements in running a business idea creatively and innovatively. Entrepreneurship training needs to be continued with other materials for the same purpose. Interested parties are expected to follow up on the results of the training so that the results become real.